Spatial Analysis Of Disaster-Resilient Multifunctional Landscape In Informal Settlements, Indonesia (Journal of Namibian Studies : History Politics Culture, 2023)
Urban landscapes with significant plant habitats become multifunctional when linked to climate disaster resilience, such as floods and strong winds. Multifunctional is spatially heterogeneous in that it provides many landscape services. This suitability depends on the biophysical area that is favorable to the conditions and interactions between landscape functions. This study aims to spatially analyze disaster-resilient multifunctional landscapes in informal settlements. Using quantitative methods, classification was carried out by applying the method of normalized difference vegetation index (NDVI) and interpolation to analyze resilient areas of floods and windstorms that are recognized as landscape functions. We mapped and analyzed the capacities to provide services of five landscape functions (flood and windstorm control, water availability, habitat; social activities) of three sub-districts in Kupang, Indonesia. The result of the study showed that the functions of flood and windstorm control synergized in several areas, while humans had a significant need for the water supply function in the area. The multifunctional landscape covered 3.51% of the study area. It is in low-lying areas with high slopes, a high level of vegetation cover, and a good level of water availability. Also, the study area had several social activities and is close to rivers and main roads. Community perceptions of landscape functions as an approach to assess the effectiveness of multifunctional landscapes as a medium for disaster resilience and avoiding environmental degradation. This calls for more appropriate policy interventions to support community disaster resilience and landscape conservation.